Fuel-free light-driven micro/nanomachines: artificial active matter mimicking nature - Villa, Katherine; Pumera, Martin (Chemical Society reviews, 2019)
The recent advances in the micro/nanomotor field have shown great progress in the propulsion of such devices by fuel-free mechanisms. Light, as an abundant and natural source, has been demonstrated to be a promising external field to wirelessly induce the motion of these tiny micro/nanomachines, without the need of any toxic fuel or complex system set-up. This tutorial review covers the most representative examples of light-driven micro/nanomotors developed so far, which self-propelled exclusively under fuel-free conditions. Their different swimming behaviors triggered by light stimuli, divided into four main categories (schooling, phototaxis, gravitaxis and directional motion), are discussed along with their similarities with the motion modes of microorganisms. Moreover, the main parameters that influence the motion of light-driven photocatalytic-based micro/nanomotors as well as alternative strategies to develop more efficient systems are also discussed.
Keywords: biomimetické materiály; katalýza; Light; Solar Energy; nanostruktury; Nanostructures; Nanotechnology; Catalysis; světlo; Biomimetic Materials; sluneční energie; nanotechnologie